EFEK UJI DAYA BUNUH EKSTRAK KULIT BUAH JERUK NIPIS (CITRUS AURANTI FOLIA) TERHADAP BAKTERI STREPTOCOCCUS MUTANS - Ulya, Miftha; Orienty, Fauzia Nilam; Hayati, Maulida (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2018)
One effort to reduce the number of dental caries in the community is needed antibacterial that can kill the bacteria Streptococcus mutans. One of the antibacterials of nature that can be used as a drug is lime (Citrus aurantifolia). The purpose of this research was to determine the effect of kill power test extract of lime peel (Citrus aurantifolia) against Streptococcus mutans bacteria, the type of research used is laboratory experimental. The samples were colonies of Streptococcus mutans bacteria obtained from University of Indonesia, with 6 treatments in each extract 12.5%, 25%, 50% and 100%. This study used 4 concentrations (12.5%, 25%, 50% and 100% as well as negative and positive control) using Kruskall-Wallis test. The results showed that there was inhibitory power and kill power extract of citrus fruits (Citrus aurantifolia) against Streptococcus mutans bacteria with a value of 0.000 <0,05. 50% concentration is the most effective concentration for bacterial inhibition and 100% concentration is the most effective concentration for killing strength of Streptococcus mutans bacteria